An Improved Sea‐Ice Velocity Retrieval Algorithm Based on 89 GHz Brightness Temperature Satellite Data in the Fram Strait. Issue 6 (17th June 2022) - Shi, Q.; Su, J.; Spreen, G.; Yang, Q.
Abstract: Fram Strait is the passageway where most drifting sea ice exits the Arctic Ocean into the North Atlantic, and the sea‐ice velocity (SIV) is the most critical parameter for the variability of the sea ice area flux through Fram Strait. Sea ice flux estimates through the Fram Strait based on satellite remote sensing exist. However, they show discrepancies, which mainly result from the sparse valid satellite observations and the increased uncertainty of sea ice motion in the Fram Strait. In order to improve the sea ice flux estimates, we develop an improved sea‐ice velocity retrieval algorithm from 89 GHz brightness temperature fields of Advanced Microwave Scanning Radiometer for EOS and AMSR2. The improved retrieval algorithm employs an adjusted size of the template window and performs bilinear interpolation on candidate windows before the matching procedure. Instead of depending on external data sources, we construct the SIV uncertainty fields depending only on the maximum correlation coefficients of the image itself. Compared with two similar Passive Microwave (PM) sea ice velocity datasets, the new sea‐ice velocity has lower bias and root‐mean‐square error with respect to buoy observations. In addition, the data density of the new SIV is 14% and 36% higher than the two reference datasets, respectively. Monthly sea ice area flux estimates through the Fram Strait are acquired with the new daily sea‐ice velocity data and the existed sea‐ice concentration. And it indicates that the improved sea ice area flux estimated by PM sea ice velocity agrees well with the Synthetic‐aperture radar‐derived sea ice area flux. Plain Language Summary: The sea ice outflux through the Fram Strait is critical for the mass balance of Arctic sea ice cover. However, previous studies tend to underestimate ice flux based on satellite data sets due to the weaker southward ice velocity with respect to buoy measurements. In order to acquire the accurate ice velocity in the Fram Strait to improve the ice flux estimates, we improve a pattern‐tracking sea ice retrieval algorithm derived from 89 GHz brightness temperature in the Fram Strait. Besides, we acquire the uncertainties with spatiotemporal variability of ice velocity based on the pattern features rather than any external data sources. This improved sea ice velocity data set will be helpful to future studies on data assimilation and model improvements. Key Points: An optimal sea ice motion tracking method based on passive microwave image in the Fram Strait has been investigated Uncertainty of sea ice velocity has been estimated based on the maximum correlation coefficient of template Improved sea ice area flux through Fram Strait during winter has been acquired based on improved sea ice velocity data sets